Critical Success Factors (CSFs) needed to Build Faculty Knowledge Sharing Systems Concentrating in Universities the Middle East - Ashraf Badawood, Dr; Hamad AlBadri, Dr (International Journal of Engineering and Technology, 2018)
The objective of this study is to assess the critical success factors needed to build faculty knowledge management systems with students by using phone texting platform. This study particularly investigates the efficacy of using phone texting platforms as primary knowledge sharing system in universities in the Middle East. Consistent with results collected and previous research, it was shown that knowledge sharing is plagued by various barriers while implementation of phone texting platforms was viable but also impaired. To ameliorate this, changes in cultural, leadership and control attitudes ought to be undertaken to ensure knowledge sharing technologies are integrated in culture as well as in the universities. Revision of government policy is also important in order to foster implementation of knowledge management systems in universities and they can also help in availing the capital outlays required for infrastructure. Furthermore, collaboration with western universities who have already impended phone texting platforms as knowledge sharing systems is also essential. Finally, training of faculty members on how to use and integrate knowledge sharing technology especially phone texting platform will help in augmenting their skills in this facet of knowledge managementÂ